HANDLING GUEST COMPLAINTS DUE TO HUMAN ERROR IN THE JAYAKARTA BALI BEACH RESORT RESIDENCE AND SPA - Ni Nyoman Rena Yani; Ni Gst Nym Suci Murni; Dewa Made Suria Antara (Politeknik Negeri Bali, 2018)
This study aims to know the kind of guest’s complaints, and find out to handle the guest’s complaint at The Jayakarta Bali Beach Resort Residence and Spa. This research focuses to complaints of human error, that was happened in all department and noted in log book from January until December of 2017. This study used qualitative approach and data collecting used are interview to (Duty Manager, Front Office Manager, Assistant of Front Office Manager, Food & Beverage Manager, Houskeeper, staff), observations, and documentations. The technique of data analysis is qualitative analysis, with detail processed of data reduction; presentation, and verification/conclusion. The result shows (1) complaints on 2017 are 51 complaints handled by Duty Manager, Front Office Manager, Assistant Front Office Manager, Guest Relation Officer and Supervisor’s Restaurant . (2) listen to all complaints guests attentively, apologized first to a guest concerned, ask the complaint that the party/staff related, explain about for guests concerned about the truth the incident, providing services full for into the hotel, and give complimentary based on levels of complaint that has happened to guests.